A food tax only minimally reduces the N surplus of Swiss agriculture. (December 2021) - Schmidt, Alena; Necpalova, Magdalena; Mack, Gabriele; Möhring, Anke; Six, Johan
Abstract: CONTEXT: Most Western-European countries exceed the critical loads for nitrogen (N) losses. High nitrogen (N) inputs make agriculture one of the largest contributors to N pollution. There might be a potential to reduce this losses with an output tax on animal products, as they have low N use efficiency and a tax has the potential to reduce the consumption of this products. OBJECTIVE: We want to assess the potential of a food tax on animal products to reduce the N surplus of Swiss agriculture. METHODS: We implemented a tax on meat and a tax on milk and meat in the agent-based model SWISSland. The model combines an agent-based model with a microeconomic model at the farm scale. To better understand the low response of the food tax, we applied in a second step a robust two-step global sensitivity analysis of abatement costs of individual model agents. RESULTS AND CONCLUSIONS: Imposing a tax led to an N surplus reduction of 2.1% where only meat was taxed and 2.3% where both milk and meat were taxed. The sensitivity analysis showed that distinct agents reacted non-uniformly to changing prices, so that the effect of the tax was sometimes even cancelled out. This calls for more differentiated policies to reduce the negative impact of N losses. SIGNIFICANCE: The overall impact of the food tax was minor as the distinct agents react not uniformly to lower producer prices. Graphical abstract: Unlabelled Image Highlights: Nitrogen surpluses of Swiss agriculture remain on a high level since the 90's. We assessed the effects of a food tax on nitrogen surplus in the agent-based model SWISSland. Food taxes on milk and meat products reduced nitrogen surpluses by 2.1% to 2.3%, respectively. A robust sensitivity analysis on different model agents revealed that distinct agents react differently to varying prices. Food taxes are not effective to reduce nitrogen surpluses as distinct farms react non-uniform to changing prices.